Impaired sex hormone homeostasis in patients with breast, prostate and testis cancer: What is the role of cadmium and lead? - Andjelković, Milena; Buha Djordjević, Aleksandra; Javorac, Dragana; Baralić, Katarina; Djukić-Ćosić, Danijela; Antonijević, Biljana; Ćurčić, Marijana; Antonijević Miljaković, Evica; Čolaković, Nataša; Aćimović, Miodrag; Bulat, Zorica (Archives of Pharmacy, 2022)
The endocrine potential of Cd and Pb, an important mechanism of their toxicity, has been established in certain hormone-dependent cancers. This study aimed to determine Cd and Pb levels in blood, tumor and healthy surrounding tissue of patients with breast, prostate and testis cancer and investigate the correlation of Cd and Pb with sex hormone levels in the patient’s blood. The study involved 55 breast, 41 prostate and 52 testis cancer patients, while healthy women (41) and men (61) represented control groups. Electrothermal atomic absorption spectrophotometry was used for Cd and Pb levels determination. Significantly higher Cd levels, i.e. lower Pb in tumor tissue compared to the healthy surrounding tissue were found in patients with breast cancer. A positive correlation was confirmed between Cd levels in the changed tissue and both human gonadotropins, and a negative correlation with estradiol, as well between Pb in tumor tissue and testosterone levels. Patients with prostate and testis cancer were characterized by significantly higher blood Cd levels compared to healthy subjects. Furthermore, significant Cd and Pb tumor tissue accumulation was shown in prostate and testis cancer patients. A significant positive correlation was found between blood Cd and estradiol levels in patients with prostate cancer. The study highlighted higher Cd level as a significant predictor of cancer, and confirmed impaired sex hormone homeostasis as pivotal mechanism of toxicity underlying the toxic effects of Cd and Pb in patients with breast, prostate and testis cancer.